Double or nothing - Sherwood, Kim, 1989- (Sherwood, Kim, 1989- Double 0 novel, 2023)
"James Bond is missing--and only the elite team of MI6 agents he trained can find him and thwart a nefarious scheme to expand worldwide terrorism--in this breathtaking new Bond novel"--